Socio-economic Empowerment of Rural Women Through Rural Tourism Projects in Jammu Region of J&K State in India. - Slathia, P. S.; Paul, N.; Nain, M. S. (Indian Journal of Extension Education, 2015)
Rural tourism is a collaboration of activities, services and amenities provided by farmers and rural people to attract tourist  to their area in order to generate extra income from their business. The present study was carried out in Surinsar and  Shamachack (Jhiri) villages which were covered under rural tourism project by the Department of Tourism, Govt. of  Jammu and Kashmir. Two groups comprising of 60 women constituted by the Department of Tourism, J&K were studied.  Data was collected on a comprehensively designed tool from 58 respondents involved in rural tourism project to study  their level of empowerment, constraints and suggestions through the personal interview technique and group discussion.  Itwas observedthat rural based tourism activities strengthened the women empowerment in socio-economic upliftment,  household decision making, enhanced participation in educational activities within and outside the state and supplement  the family income. Education and extension contact have been found positively correlated with women empowerment  under rural based tourism activities.
Keywords: Tourism; decision making; empowerment